ANALISIS PENGARUH INFLASI TERHADAP LAJU PERTUMBUHAN EKONOMI DI KOTA JAMBI - Prima Audia Daniel (Ekonomis: Journal of Economics and Business, 2018)
In an economy of a country or region are certainly not apart from a problem that intertwined and mutually influence each other. These conditions always happen in all countries that there is in the world and not apart of this also on the Government of the city of Jambi. The economy of the city of Jambi who still has not shown the consistency of course is still influenced by other factors are interlinked, for instance variable inflation. Inflation is indeed directly does not affect economic growth however indirectly to provide disruption in spur economic growth. On the basis of things that writers do this research. the purpose of this research is; 1) analyzing the rate of growth of inflation and economic growth that occurred in the city of Jambi; 2) analyse the influence of inflation towards economic growth in the city of Jambi; 3) and see the relationship of inflation with economic growth in the city of Jambi. This research was conducted with the use of quantitative and qualitative approaches and utilizing secondary data becomes available. analytical tools used in this research is a simple linear regression and correlation of person who used to see the influence and relationship variables infalsi against economic growth. From the results of the discussion indicates that the inflassi effect negatively to economic growth and inflation have a negative relationship with economic growth. This means that rising inflation effect on the rate of economic growth in the city of Jambi. Keywords: inflation, economic growth